Respon Remaja Lelaki Suka Lelaki (LSL) dengan Status HIV Positif terhadap Pencegahan Penularan HIV kepada Pasangan - Fauziyah Fauziyah; Zahroh Shaluhiyah; Priyadi Nugraha Prabamurti (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: In Jambi City, the cases of HIV-positive in MSM increased in the people aged 19-24 years old by 35.1%. It affected on the prevention of HIV transmission. The research was conducted in 2016 and aimed to understand the response of teenage MSM with the status of HIV-positive to the prevention of transmission to the partner.Method: The research method was qualitative with the design of case study. The sampling technique was purposive sampling with the data collection using in-depth interview. The main informants were teenage MSM with HIV-positive of 7 persons. The triangulation informants were the chief of Kanti Sehati Foundation, the chief of the Community Group of Field Outreach in Jambi City.Results: The resarch results show that the response when they initially found themselves infected by HIV-positive was a rejection to their status of HIV-positive. Their responses were shocked, surprised, and confused. They expressed their emotion in the form of stress and depression. Status revealation to their partners and closest ones had not been performed fully since they were worried about the rejection from their partners. The response to ARV obedience has been good, but the response to HIV prevention using condoms had not been consistent partially because they were mostly under the effect of alcohol. Then, the response to post-HIV behavior, in few people, showed their inability to prevent the transmission based on the standard. Most of them still experienced the stigma from their families, and physical violence from society.Keywords: MSM response, teenage, HIV, HIV Prevention